2020
DOI: 10.3390/s20040962
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Sensor Fault Diagnosis for Maintenance in Railway Traction Drives

Abstract: Due to the importance of sensors in railway traction drives availability, sensor fault diagnosis has become a key point in order to move from preventive maintenance to condition-based maintenance. Most research works are limited to sensor fault detection and isolation, but only a few of them analyze the types of sensor faults, such as offset or gain, with the aim of reconfiguring the sensor in order to implement a fault tolerant system. This article is based on a fusion of model-based and data-driven technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…It is worth mentioning that the information redundancy added to AI techniques make possible to build a complete CM platform, from data acquisition (DA) to prognostics assessment (PA) levels. • Hybrid methodology: As the aforementioned active supervision techniques have their pros and cons, a new trend has emerged, which tries to integrate together these complementary methods in order to achieve a better performance [41,42]. It is commonly agreed that hybrid schemes would provide better solutions to a complex system.…”
Section: Fundamentals Of Active Supervision In Electric Drivesmentioning
confidence: 99%
“…It is worth mentioning that the information redundancy added to AI techniques make possible to build a complete CM platform, from data acquisition (DA) to prognostics assessment (PA) levels. • Hybrid methodology: As the aforementioned active supervision techniques have their pros and cons, a new trend has emerged, which tries to integrate together these complementary methods in order to achieve a better performance [41,42]. It is commonly agreed that hybrid schemes would provide better solutions to a complex system.…”
Section: Fundamentals Of Active Supervision In Electric Drivesmentioning
confidence: 99%
“…Embedded sensors, software, controllers, connectivity, breakthroughs in networking, edge and fog computing, cloud technology, faster CPUs, cheaper memory, energy efficiency, and miniaturisation are all converging to create low-cost processing power and data storage everywhere and they became the key enabling technologies fuelling up the evolution in the paradigms [32][33][34]. As presented in Merluzzi and Brunetti [35] the "Reliability-Centered Maintenance" represents a systematic approach to evaluate a facility's equipment and resources to best mate the two and result in a high degree of facility reliability and costeffectiveness.…”
Section: Prescriptive Maintenance and Shared Valuementioning
confidence: 99%
“…Based on the literature review, it can be concluded that a MEMS-type acceleration sensor has not been used so far in the way presented by the author for positioning the electrohydraulic drive. The authors of the above-mentioned papers focused mainly on the use of this type of sensor for diagnostics of various types of hydraulic systems, examining parameters such as vibrations [ 19 , 20 , 21 , 22 ]. Other popular applications are measurements of changes in angular position, where the signal from the acceleration sensor is combined with the signal from a gyroscope, among others.…”
Section: Introductionmentioning
confidence: 99%